Looted letters. Book culture of Ḥafṣid Ifrīqiya (1229-1574) and Arabic manuscripts in early modern Europe after the sack of Tunis (1535) - Hinrichsen, L (2021)
The present thesis is based on the study of the Arabic manuscripts looted during the sack of Tunis in 1535, and then brought to Europe and sold or donated to important scholars and institutions in Italy, France, and the Habsburg Empire. The manuscript corpus examined here is thus delimited by a common provenance and collection history.